The factor structure of the adapted who quality of life bref questionnaire in a sample of adolescents in Nigeria (2018)
The World Health Organization’s Quality of Life Instrument (WHOQOL-BREF) is widely validated and popularly used in assessing perceived quality of life (QOL) of adolescents and the general population. Though the WHOQOL-BREF has been used in some studies in Nigeria, its theoretical structure has not been comprehensively investigated. This study examined the factor structure of the Adopted WHOQOL-BREF questionnaire and it theoretical structure in a large sample of adolescents in Nigeria. Data on demographic characteristics and QOL were extracted from 1,963 adolescents who participated in a state-wide study on psychosocial functioning and quality of life of adolescents in Benue State, Nigeria. Descriptive statistics were used to present the distribution of the data while Cronbach’s alpha and Polychoric ordinal alpha were used to describe the internal consistency (reliability) of the adapted WHOQOL-BREF and alpha value of 0.700 was considered reliable. Structural analysis was performed to extract the underlying factors while confirmatory factor analyses were used to assess some hypothesized structure of the adapted WHO-QOL BREF. Relative Chi-square test value ≤3.0 was regarded a good fit while multiple fit indexes with values ≥0.90 (for acceptable fit) were used for assessing diverse aspects of the models. All analyses were performed at 5% significance level using IBM SPSS statistics version 20, R package and AMOS version 21. Participants were mostly male (54.8%) and 14.7±1.4 years old with 51.0% residing in rural areas. The overall internal consistency of the 4-factor model was 0.862 (for Cronbach’s Alpha) and 0.989 (for Polychoric Alpha) while the 2-factor model had 0.870 (for Cronbach’s Alpha) and 0.990 (for Polychoric Alpha). The Cattelle’s Scree plot, Horn’s parallel analysis and the confirmatory factor analysis revealed a 2-factor model as the best model for the WHO-QOL BREF. The 23-item 2-factor structure had a relative Chi-square test value with all fit indices within the acceptable range. The adapted WHO QOL BREF can be safely used to assess quality of life among Adolescents in Nigeria and related settings. Using the two factors extracted in the present study may yield better results in settings similar to the present study location.